2009
DOI: 10.1021/la903922y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Confinement on the Mesoscale and Macroscopic Swelling of Thin Block Copolymer Films

Abstract: We report on the swelling behavior and the corresponding morphological behavior of cylinder-forming polystyrene-b-polybutadiene diblock copolymers, which are confined to several layers of structures. The equilibration of thin films has been done under controlled atmosphere of a nonselective solvent. In situ spectroscopic ellipsometry measurements revealed more than 10% increase of the solvent uptake with decreasing film thickness. With scanning force microscopy of the microphase separated patterns in quenched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
88
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 53 publications
2
88
0
Order By: Relevance
“…It is well known that block copolymers (BCPs) can self‐assemble into nanometer‐sized domains due to thermodynamic instability . One important method by which such self‐assembly structures can be further adjusted is solvent vapor annealing (SVA) . Once a BCP film is exposed to solvent vapor, polymer chains will absorb solvent molecules and the Flory–Huggins interaction parameter between polymer blocks or polymer blocks and the substrate will be significantly reduced, which results in the improvement of their mobility and lowering of the barrier to rearrangement of BCP .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that block copolymers (BCPs) can self‐assemble into nanometer‐sized domains due to thermodynamic instability . One important method by which such self‐assembly structures can be further adjusted is solvent vapor annealing (SVA) . Once a BCP film is exposed to solvent vapor, polymer chains will absorb solvent molecules and the Flory–Huggins interaction parameter between polymer blocks or polymer blocks and the substrate will be significantly reduced, which results in the improvement of their mobility and lowering of the barrier to rearrangement of BCP .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] One important method by which such self-assembly structures can be further adjusted is solvent vapor annealing (SVA). [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Once a BCP film is exposed to solvent vapor, polymer chains will absorb solvent molecules and the Flory-Huggins interaction parameter between polymer blocks or polymer blocks and the substrate will be significantly reduced, which results in the improvement of their mobility and lowering of the barrier to rearrangement of BCP. 14,15 Gu and colleagues investigated the effect of processing history on the morphology evolution in polystyrene-block-poly(2-vinylpyridine) (PS-b-P2VP) films, and they indicated that the rearrangement of BCP microdomains towards equilibrium structure took place above a threshold swelling ratio.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Analysis of the phase behavior under controlled solvent vapor treatment allowed to gain important insights into the mechanisms of microphase separation of conjugated polymers, 5 and of microdomain reorientation and ordering under combined application of solvent annealing and of electric field. [55][56][57][58] Furthermore, confinement effects on the microphase separation and swelling of thin 24,59 and thick 55,37 block copolymer films have become evident in the thickness-dependent swelling as well as in heterogeneous swelling of block copolymer films. 24,60,61 In the last years similar climate-controlled solvent-vapor annealing devices have been adopted and successfully exploited by several research groups.…”
Section: Introductionmentioning
confidence: 99%
“…In such a case, solvent annealing provides an attractive alternative to thermal annealing. Since sufficient mobility of the copolymer chains is easily induced by solvent annealing at room temperature without the danger of degradation only with the film thickness changing, the way of solvent annealing has been used more and more widely . However, in most conventional BCP assembly processes undergone solvent annealing, a prolonged annealing approach is reported .…”
Section: Introductionmentioning
confidence: 99%